Evaluation of Lifetime and Sulfur adsorption on Zinc Oxide (ZnO) at Desulfurizer of Fertilizer Industry - Fadhilah Rizki; Rizky Vasya Ramadhanty; Lia Cundari; Dwi Anggraini; Muhammad Riduansyah (Universitas Tribhuwana Tunggadewi Malang, 2026)
Fertilizer Industry has an ammonia unit to produce ammonia as the main raw material for urea production. The sulfur removal process occurs in the desulfurizer in the feed treating section to minimize ammonia production failure due to the toxic nature of sulfur for the catalyst in the reforming section. When the adsorbent is saturated in one of the desulfurizers, the desulfurizer position will be swapped and replaced with a new ZnO adsorbent. Lifetime evaluation of the adsorbent as well as analysis of the adsorption characteristics of the 108-DB desulfurizer were conducted to determine the adsorption performance by the adsorbent. Zinc Oxide (ZnO) adsorbent as of August 23, 2022 desulfurizer is still suitable for use and it is necessary to replace the new ZnO adsorbent when the fertilizer industry is Turn Around schedule, it is carried out in July 2023 in accordance with the design lifetime data of 3-4 years. The sulfur adsorption process of PUSRI-IIB feed treating section by ZnO adsorbent in desulfurizer follows the second-order kinetics model with the adsorption rate constant (k) value obtained as -0.3339 (month-1). The adsorption isotherm that takes place follows the Langmuir isotherm model and belongs to the type of chemical adsorption (chemisorption) with the maximum adsorption capacity (qe) and Langmuir adsorption constant (KL) values of 0.0629 mg/g.hr and 3.283977 L/mg, respectively.